ANALISA KANDUNGAN RHODAMIN B DAN FORMALIN PADA GULA MERAH SERTA PENGETAHUAN DAN SIKAP PEDAGANG DI PASAR TRADISIONAL KECAMATAN MEDAN BARU TAHUN 2013 - emma sihombing; wirsal hasan; irnawati marsaulina (Lingkungan dan Kesehatan Kerja, 2014)
Rhodamine B and formaldehyde is colouration substance and preservative substance that prohibits to be utilized in food product. But there are still traders using rhodamine B and formaldehyde in food products and beverages. Brown sugar is one of the food ingredients that are often encountered in daily life. The purpose of this research is to determine the rhodamine B dye and preservative formaldehyde in brown sugar in the traditional market sub-district Medan Baru in 2013 and determine the level of knowledge and attitude of brown sugar’s traders. This research is a simple descriptive. The method used is applicable in the examination of laboratory in brown sugar with chromatography paper (rhodamine B) and destilation method (formaldehyde) , interview using a questionnaire to 12 traders in traditional market sub-district Medan Baru. Based on the results of laboratory examination of the rhodamine B dye and preservative formaldehyde in brown sugar is known that all (100%) of brown sugar does not contain dyes rhodamine B and preservative formaldehyde. The results of questionnaire showed that traders with knowledge of enough category as many as 9 (75.0%), traders with knowledge of good category as many as 2 (16.7%) and traders with knowledge of less category as many as 1 (8.3%). Traders with attitude of enough category as many as 7 (58.3%), traders with attitude of good category as many as 4 (33.3%) and traders with attitude of less category as many as 1 (8.3%). Traders are advised to pay more attention to the brown sugar to be sold and the buyer to be more careful selection of the brown sugar that is not harmful for consumption. To the government to more tighten supervision and checks periodically on brown sugar so there is no use dye substances nor preservative not allowed as rhodamine B and formaldehyde.